High Throughput Analysis Reveals Changes in Gut Microbiota and Specific Fecal Metabolomic Signature in Hematopoietic Stem Cell Transplant Patients - Soumaya Kouidhi; Nessrine Souai; Oumaima Zidi; Amor Mosbah; Amel Lakhal; Tarek Ben Othmane; Dorra Belloumi; Farhat Ben Ayed; Elias Asimakis; Panagiota Stathopoulou; Ameur Cherif; George Tsiamis (Microorganisms, 2021)
There is mounting evidence for the emerging role of gut microbiota (GM) and its metabolites in profoundly impacting allogenic hematopoietic stem cell transplantation (allo-HSCT) and its subsequent complications, mainly infections and graft versus host-disease (GvHD). The present study was performed in order to investigate changes in GM composition and fecal metabolic signature between transplant patients (n = 15) and healthy controls (n = 18). The intestinal microbiota was characterized by NGS and gas chromatography–mass spectrometry was employed to perform untargeted analysis of fecal metabolites. We found lower relative abundances of Actinobacteria, Firmicutes, and Bacteroidetes and a higher abundance of Proteobacteria phylum after allo-HSCT. Particularly, the GvHD microbiota was characterized by a lower relative abundance of the short-chain fatty acid-producing bacteria, namely, the Feacalibacterium, Akkermansia, and Veillonella genera and the Lachnospiraceae family, and an enrichment in multidrug-resistant bacteria belonging to Escherichia, Shigella, and Bacteroides. Moreover, network analysis showed that GvHD was linked to a higher number of positive interactions of Blautia and a significant mutual-exclusion rate of Citrobacter. The fecal metabolome was dominated by lipids in the transplant group when compared with the healthy individuals (p < 0.05). Overall, 76 metabolites were significantly altered within transplant recipients, of which 24 were selected as potential biomarkers. Furthermore, the most notable altered metabolic pathways included the TCA cycle; butanoate, propanoate, and pyruvate metabolisms; steroid biosynthesis; and glycolysis/gluconeogenesis. Specific biomarkers and altered metabolic pathways were correlated to GvHD onset. Our results showed significant shifts in gut microbiota structure and fecal metabolites characterizing allo-HSCT.